2014
DOI: 10.1097/01.eja.0000435016.83813.aa
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guidance of needle tip position for femoral nerve blockade

Abstract: The GIPM was seen in the majority undergoing ultrasound-guided femoral nerve blockade, even when the lateral part of the femoral nerve was not visualised. Using the lateral segment of GIPM as a target for needle tip location in an in-plane lateral to medial approach of the femoral nerve deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…And the sample size ranged from 50 to 112. And 10 included studies were conducted in China, [16,17,19,20,22–27] 1 in Spain, [14] 1 in the United States, [15] 1 in South Korea [18] and 1 in Denmark. [21]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the sample size ranged from 50 to 112. And 10 included studies were conducted in China, [16,17,19,20,22–27] 1 in Spain, [14] 1 in the United States, [15] 1 in South Korea [18] and 1 in Denmark. [21]…”
Section: Resultsmentioning
confidence: 99%
“…[12,13] It has been confirmed that acupoints such as Neiguan (PC6), Laogong (PC8), Waiguan (SJ5) Zusanli (ST36), Hegu (LI4), and Quchi (LI11) can be used for reducing PONV. [14–27] The basic theory of action mechanism is related to activating meridians by acupuncture. [28] Acupoints could be stimulated by acupuncture needle, electrical stimulation, and acupressure and so on.…”
Section: Introductionmentioning
confidence: 99%
“…To visualise the femoral nerve, we slightly modified the method described by Fanara et al (2014) and Szucs et al (2010). First, the anterior superior iliac spine was located by palpation and the transducer was positioned over this bony landmark.…”
Section: Identification Of the Femoral Nervementioning
confidence: 99%
“…[ 13 ] FNB is done blindly using a nerve stimulator with a needle. [ 14 ] Besides, the emergency physicians with good anatomic knowledge could be trained for this technique easily. Hence, RA can be preferred over general anesthesia (GA) for these surgeries.…”
Section: Introductionmentioning
confidence: 99%